Effects of Aerobic Exercise on Happiness Among University Students - Seyed Mohammad Masoud Shushtarian; Sahbaeiroy Faezeh (Journal of Health Statistics Reports, 2026)
Background: University students may experience academic and social stressors that adversely affect psychological well-being and happiness. Aerobic exercise may provide an accessible strategy for promoting positive mental health. This study investigated the effect of a structured aerobic exercise program on happiness among female university students. Methods: In this one-group pretest–posttest quasi-experimental study, 80 female students aged 18-22 years participated in a supervised aerobic exercise program. The intervention comprised 16 sessions over 8 weeks, with two 45-minute sessions per week, performed at approximately 60% of maximum heart rate. Happiness was assessed using the 29-item Oxford Happiness Questionnaire before the intervention and one month after its completion. Data were analyzed using descriptive statistics and a paired-samples t-test in SPSS version 24. Results: Following the intervention, the proportion of students with high or very high happiness increased from 40.0% at baseline to 63.75%, while the proportion with low or moderate happiness decreased from 60.0% to 36.25%. The paired-samples t-test demonstrated a statistically significant improvement in happiness following the intervention (t (79) =8.02, P